Photoluminescence properties of lead selenide produced by selenization and a solvothermal method - Kim, Jungdong; Ahn, Hak-Young; Kim, Seung Gi; Oh, Eunsoon; Ju, Byeong-Kwon; Choi, Won Jun; Cho, So-Hye (IOP PUBLISHING LTD, 2017)
We studied temperature-dependent photoluminescence (PL) spectra of lead selenide (PbSe) dendrites and cubes grown by a solvothermal method. Their PL peaks were located at similar to 8 mu m at 10 K with a full width at half maximum (FWHM) of 10 meV. Using the temperature-dependent FWHM values, we obtained carrier-phonon coupling coefficients for PbSe. We also demonstrated mechanochemical synthesis of polycrystalline PbS nanoparticles and their successful conversion into a PbSe layer composed of nanocrystals by a selenization process with thermal treatment. The nanocrystals were found to be formed by the orientation alignment of small grains in the process. The PL peak energies of the PbSe layers as well as the PbSe dendrites and the cubes agreed well with their absorption edges in the transmission spectra, indicating that the photoluminescence originates from the band-edge emission. The band-edge emissions hold promise for the development of potential mid-infrared light sources using PbSe fabricated by these methods.
Keywords: PBSE; NANOCRYSTALS; LINEWIDTHS; GAP